Tritrophic interaction between whiteflies, insect pathogenic fungi and host plant : biology of whitefly, Bemisia afer - Cavén, Ethel (SLU/Dept. of Ecology, 2007)
The study was preformed at the International Potato Centre, CIP, in the capital of Peru, Lima on the west coast of South America and the Ecology Department, SLU, Uppsala, Sweden.